(untitled) (Indian Journal of Integrative Medicine, 2024)
Background and Objectives: The World Health Organization (WHO) estimates that at least 9 million people around the world die from excessive blood pressure each year, either directly or indirectly. In a study conducted in India, anti-hypertensive drugs were discovered to be the medications most commonly linked to adverse drug reactions (ADRs). This research was conducted to evaluate the immediate impact of cephalic compress on heart rate variability (HRV) in hypertensive people and thus to authenticate the clinical understanding of its effect. Methods: 100 participants were randomly kept into two groups: group-1 (n=50) and group-2 (n=50). Group 1 underwent cephalic compress for 15 minutes and Group 2 was asked for general relaxation for 15 minutes. Before and soon after the intervention, the subjects’ blood pressure and HRV were measured. This randomized controlled trial was registered in the Clinical Trials Registry-India (CTRI/2021/12/038539) on 9/12/2021. Results: The data analysis showed significant decrease in SBP(p<0.01), DBP(p<0.01), LF (p<0.01), LF/HF (p<0.01) and a significant increase in Average RR(p<0.005), NN50(p<0.01), RMSSD(p<0.01), HF(p<0.01) in HRV assessment after giving cephalic compress. Interpretation & Conclusion: This study shows that cephalic compress enhances parasympathetic activity and improves sympathovagal balance in hypertensive individuals. Thus, the application of cephalic compress is the adjuvant management of essential hypertension.